2000
DOI: 10.1046/j.1439-0523.2000.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

High genetic diversity of Spanish common wheats as judged from gliadin alleles

Abstract: Gliadin alleles were identified in 100 common wheat cultivars registered and/or grown in Spain during the last 40 years. A very high level of genetic polymorphism was found: in total, 103 allelic variants including one null‐allele were found at the six major Gli loci in the Spanish wheats studied. An average genetic diversity for these six loci was found to be higher (H=0.844) than in any group of wheat cultivars studied previously. Spanish wheats bred in Spain demonstrated even higher genetic diversity (H=0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 17 publications
1
32
0
1
Order By: Relevance
“…More than 80% of these proteins belong to gliadins and glutenins, defined as gluten proteins (GP) [3,4]. Gliadins and glutenins of individual wheat genotypes may be separated into dozens of protein bands using onedimensional electrophoretic techniques (A-PAGE or SDS-PAGE), whereas hundreds of spots may be developed using 2D electrophoresis (IEF/SDS-PAGE) [5,6]. Traditionally, gliadins are divided into α, β, γ, ω-5 and ω-1.2 subclasses based on decreased electrophoretic mobility in A-PAGE conditions.…”
Section: Introductionmentioning
confidence: 99%
“…More than 80% of these proteins belong to gliadins and glutenins, defined as gluten proteins (GP) [3,4]. Gliadins and glutenins of individual wheat genotypes may be separated into dozens of protein bands using onedimensional electrophoretic techniques (A-PAGE or SDS-PAGE), whereas hundreds of spots may be developed using 2D electrophoresis (IEF/SDS-PAGE) [5,6]. Traditionally, gliadins are divided into α, β, γ, ω-5 and ω-1.2 subclasses based on decreased electrophoretic mobility in A-PAGE conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophoresis of HMW GS was car ried out by the procedure of Laemmli [18] in 10 % resolving gel. Gliadin alleles were identified using the catalogue of Metakovsky [3] supplemented by alleles presented in further studies [12,14,19]. The Gli B5b allele was identified from the charac teristic pattern (two ω components), as presented in [14].…”
mentioning
confidence: 99%
“…Gliadin alleles were identified using the catalogue of Metakovsky [3] supplemented by alleles presented in further studies [12,14,19]. The Gli B5b allele was identified from the charac teristic pattern (two ω components), as presented in [14]. Cultivars lacking these components carry the Gli B5a allele (null allele) [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins have been widely studied in cereals due to its relations to bread-making quality (Payne et al, 1982). These studies have shown high levels of genetic variability, highlighting their possibility in the study of genetic resources (Metakovsky et al, 2000) and varietal identification (Zillman & Bushuk, 1979).…”
Section: Introductionmentioning
confidence: 99%